Epidemiology of traumatic brain injury in children 15 years and younger in South-Eastern Norway in 2015–16. Implications for prevention and follow-up needs. (March 2021) - Dahl, Hilde Margrete; Andelic, Nada; Løvstad, Marianne; Holthe, Ingvil Laberg; Hestnes, Morten; Diseth, Trond H.; Myhre, Mia Cathrine
Abstract: Objective: This retrospective study aimed to describe the volume, severity, and injury mechanism of all hospital-admitted pediatric traumatic brain injury (pTBI) at Oslo University Hospital (OUH), emphasizing consequences for prevention and factors indicating a need for follow-up programs. Method: Data were extracted from the OUH Trauma registry on 176 children, 0–15 years old, admitted to OUH in 2015 and 2016 with a pTBI diagnosis. The dataset contains demographic data, injury mechanism, type, and severity (Glasgow coma scale, GCS; abbreviated injury scale, AIS; injury severity score, ISS), ICD-10 diagnosis codes, level of treatment, and destination of discharge. Results: 79.5% had mild, 9% moderate, and 11.4% severe TBI. The incidence of hospital-treated pTBI in Oslo was 29 per 100, 000 per year. The boy: girl ratio was 1.9:1, but in the young teenage group (14–15 years), the ratio was 1:1. Intracranial injury (ICI) identified on CT/MRI was associated with extended hospital stays, with a median of 6 days compared to 1 day for patients without ICI. 27% of the patients assessed as mild TBI at admission had ICI. Children below eight years of age had a higher incidence of moderate and severe ICI from trauma (53% v.s. 28% in children ≥ eight years). Conclusion: The injury characteristics of hospital-treated pTBI are in line with other European countries, but we find the boy-girl ratio different as young teenage girls seem to be catching up with the boys. ICI and length of stay should be considered when deciding which patients need follow-up and rehabilitation. Highlights: Monitoring changes in risk-seeking behavior is significant regarding preventing TBI. Children under eight years old suffer more severe intracranial injuries (ICI) from TBI. Follow up is needed for ICI or prolonged symptoms after TBI of all severity grades.